(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this study was used Bacillus spp. isolate after collection and identification and screening as the best isolate for protease production by using skim milk agar as screening media then the isolate that give the highest proteolytic activity was chosen and the protease was partially purified by the ammonium sulfate and sephadex G-50 to give activity 320 and 640 U/ml subsequently , then the activity was examined in vitro with formula by using skim milk agar as a screening media to detect of protease activity within the formula the result proved increasing of protease activity by increasing of clearing zone around well of well diffusion assay of skim milk and can used this formula for medical application.